Shifting fish consumption preferences can impact coral reef resilience in the Maldives: a case study. (December 2021) - Yadav, Shreya; Fisam, Abdulla; Dacks, Rachel; Madin, Joshua S.; Mawyer, Alexander
Abstract: People's preferences and choices around food directly influence their resource use and the resilience of dynamically linked natural and human systems. In this study we examine fish preference and consumption patterns in Dhaalu atoll, Maldives, where fisheries have experienced rapid change in response to tourism and development. We find that reef fishes are now a significant part of local diets, with 58% of interview respondents preferring to eat reef fish over the historically more popular and sustainable tuna. Our findings suggest that preferences, which vary with gender and age, are an important yet underutilized indicator of changing pressures on reefs. While demand from nearby resorts currently drives the majority of reef fishing in these islands, we document seasonal spikes in the local catch and consumption of reef fishes and record an informal network of sharing that should be considered while developing management plans. Rising levels of reef fish consumption could have significant environmental impacts in the Maldives with implications for island food security and community wellbeing.